2020
DOI: 10.14687/jhs.v17i4.6077
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the volleyball team ranking in the 2016 Rio Olympics by artificial neural network and linear model

Abstract: This study was conducted to estimate the Olympic ranking of the games played in the qualifying groups by the countries that were qualified for the 2016 Rio Olympics in volleyball branch by analyzing with the developed artificial neural networks (ANN) and linear equation model. In the study, the difficulty level of all games (n=324) that total 22 teams played in the qualifying for the 2016 Rio Olympics in volleyball branch (11 female and 11 male volleyball teams)  and International Volleyball Federation (FIVB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…No study on the evaluation of the set results in volleyball by ANN model was found in the literature, and the studies for the evaluation of the games of other branches were limited. In a similar study, Akarçeşme et al, (2020) predicted the volleyball team ranking in the Rio Olympics via the ANN model developed according to nine different input variables. Volleyball team ranking in the Rio Olympics was predicted with an accuracy of over 98% in women's category and over 99% in men's via the ANN model developed as a result of the study by Akarçeşme et al, (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No study on the evaluation of the set results in volleyball by ANN model was found in the literature, and the studies for the evaluation of the games of other branches were limited. In a similar study, Akarçeşme et al, (2020) predicted the volleyball team ranking in the Rio Olympics via the ANN model developed according to nine different input variables. Volleyball team ranking in the Rio Olympics was predicted with an accuracy of over 98% in women's category and over 99% in men's via the ANN model developed as a result of the study by Akarçeşme et al, (2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Akarçeşme et al, (2020) predicted the volleyball team ranking in the Rio Olympics via the ANN model developed according to nine different input variables. Volleyball team ranking in the Rio Olympics was predicted with an accuracy of over 98% in women's category and over 99% in men's via the ANN model developed as a result of the study by Akarçeşme et al, (2020). In another study, Tümer & Koçer (2017) predicted Turkish Volleyball League with an accuracy of 98% by using ANN model (Tümer & Koçer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since particularly the total scores had a high correlation with most of the other variables, the total scores in question (match, set, t_pt) were not included in the model. Consequently, the feedforward regression model that best estimated (with the lowest error rates: RMSE, MAD and the highest accuracy values) the league standing variable through sigmoid activation function (preferred due to its ability to output values within the 0-1 range) was determined from the input layer that Gazi Journal of Physical Education and Sports Sciences, 2024, 29 (3), [202][203][204][205][206][207][208][209] was generated by using the total 23 input variables and the output variable. The training set included the results of the first 4 seasons and the test set includes that of the last season.…”
Section: Methods Data Collectionmentioning
confidence: 99%